Expanded newborn screening program in Slovenia using tandem mass spectrometry and confirmatory next generation sequencing genetic testing - Lampret Barbka Repič; Remec Žiga Iztok; Torkar Ana Drole; Tanšek Mojca Žerjav; Šmon Andraz; Koračin Vanesa; Čuk Vanja; Perko Daša; Ulaga Blanka; Jelovšek Ana Marija; Debeljak Maruša; Kovač Jernej; et al. (Sciendo, 2020)
In the last two decades, the introduction of tandem mass spectrometry in clinical laboratories has enabled simultaneous testing of numerous acylcarnitines and amino acids from dried blood spots for detecting many aminoacidopathies, organic acidurias and fatty acid oxidation disorders. The expanded newborn screening was introduced in Slovenia in September 2018. Seventeen metabolic diseases have been added to the pre-existing screening panel for congenital hypothyroidism and phenylketonuria, and the newborn screening program was substantially reorganized and upgraded.